2019
DOI: 10.1002/hep4.1452
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Promotes Hepatic Stellate Cell Activation by Regulating Plasma Membrane Localization of TGFβ Receptor 2

Abstract: Transforming growth factor β (TGFβ) induces hepatic stellate cell (HSC) differentiation into tumor-promoting myofibroblast, although underlying mechanism remains incompletely understood. Focal adhesion kinase (FAK) is activated in response to TGFβ stimulation, so it transmits TGFβ stimulus to extracellular signal-regulated kinase and P38 mitogenactivated protein kinase signaling. However, it is unknown whether FAK can, in return, modulate TGFβ receptors. In this study, we tested whether FAK phosphorylated TGFβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…In the present study, we found that integrin β1-FAK is involved in the classical TGFβ/Smad-dependent pathway rather than the p38 MAPK pathway. Also, our data on the binding between integrin β1 and TGFβRI suggested It was reported that FAK and integrin β3 bind to TGFβRII in stellate hepatic cells 39 and breast cancer cells 40 . Here, we detected that in EZH2 high expressing breast cancer cells, FAK and integrin β1 bound to TGFβRI rather than TGFβRII and that FAK phosphorylated TGFβRI.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the present study, we found that integrin β1-FAK is involved in the classical TGFβ/Smad-dependent pathway rather than the p38 MAPK pathway. Also, our data on the binding between integrin β1 and TGFβRI suggested It was reported that FAK and integrin β3 bind to TGFβRII in stellate hepatic cells 39 and breast cancer cells 40 . Here, we detected that in EZH2 high expressing breast cancer cells, FAK and integrin β1 bound to TGFβRI rather than TGFβRII and that FAK phosphorylated TGFβRI.…”
Section: Discussionsupporting
confidence: 51%
“…It was reported that FAK and integrin β3 bind to TGFβRII in stellate hepatic cells 39 and breast cancer cells 40 . Here, we detected that in EZH2 high expressing breast cancer cells, FAK and integrin β1 bound to TGFβRI rather than TGFβRII and that FAK phosphorylated TGFβRI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have implicated that FAK transmits extracellular stimuli to phosphatidylinositol 3-kinase (PI3K)/Akt, extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and Rho-family small guanosine triphosphatase signaling, contributing to the fundamental cell biological processes, such as cell adhesion, migration, proliferation, and survival. 21 FAK is a nonreceptor tyrosine kinase that participates in FA complex formation. Its dysregulation is found in various types of cancer in relation to tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are the principal adhesion receptors that transfer signals between ECM pathways and cytoplasmic domains across the cell plasma membrane. FAK is also activated in response to TGF-β1 activation and also other cytokines and growth factors [ 9 , 59 ]. Consistent with the current study’s findings, TGF-β1 activates HSCs to produce fibronectin, α-SMA, and CTGF, markers of HSC activation.…”
Section: Discussionmentioning
confidence: 99%